2017
DOI: 10.1088/1361-6560/62/11/4300
|View full text |Cite
|
Sign up to set email alerts
|

Reducing 4DCBCT imaging time and dose: the first implementation of variable gantry speed 4DCBCT on a linear accelerator

Abstract: Abstract. Four dimensional cone beam computed tomography (4DCBCT) uses a constant gantry speed and imaging frequency that are independent of the patient's breathing rate. Using a technique called Respiratory Motion Guided 4DCBCT (RMG-4DCBCT), we have previously demonstrated that by varying the gantry speed and imaging frequency, in response to changes in the patient's real-time respiratory signal, the imaging dose can be reduced by 50-70%. RMG-4DCBCT optimally computes a patient specific gantry trajectory to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…We have previously demonstrated the feasibility of modifying the gantry velocity and projection time interval in response to a patient's real‐time respiratory signal on an Elekta linac, indicating the potential to move our dual adaptive protocol from simulation through to experimental realization. The movements of the gantry are smooth, not requiring rapid repositioning, and are within the mechanical constraints of a standard linac.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated the feasibility of modifying the gantry velocity and projection time interval in response to a patient's real‐time respiratory signal on an Elekta linac, indicating the potential to move our dual adaptive protocol from simulation through to experimental realization. The movements of the gantry are smooth, not requiring rapid repositioning, and are within the mechanical constraints of a standard linac.…”
Section: Discussionmentioning
confidence: 99%
“…That is, for cardiaconly motion guided CBCT imaging we considered the effect of arrhythmias on image quality and scan time, 17 while for respiratory-only motion guided CBCT imaging we looked to encompass irregular breathing by examining 112 breathing traces from 24 lung cancer patients. 14 We have previously demonstrated the feasibility of modifying the gantry velocity and projection time interval in response to a patient's real-time respiratory signal on an Elekta linac, 15,16 indicating the potential to move our dual adaptive protocol from simulation through to experimental realization. The movements of the gantry are smooth, not requiring rapid repositioning, and are within the mechanical constraints of a standard linac.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that by varying the gantry speed and imaging frequency in response to changes in the patient's real-time respiratory signal, the imaging dose can be reduced by 50% to 70%. 7 IMRT has become an important radiation-delivery technique in the management of H&N cancers. It conforms the prescribed doses to the target volumes of complex shapes while sparing the adjacent critical structures without compromising the target coverage.…”
Section: Human Papillomavirus and Hnscc Cancersmentioning
confidence: 99%